Чи є підстави відзначати 1000-ліття Бояна? - Чепа, М.-Л. (Слово і Час, 2011)
У статті розглядається гіпотеза Вельтмана-Чепи про тотожність особи Бояна й літописного
Яня. На матеріалах історичних, літературних, етнопсихологічних артефактів автор показує
багатогранність особистості Бояна – поета, митця, мислителя, воїна, громадянина Руси-України;
обґрунтовує необхідність відзначення на державному та міжнародному рівні 1000-го ювілею
Бояна-Яня у 2016 році. The article considers the Veltman-Chepa hypothesis on identity of the real Boyan and the legendary
Yan who was mentioned in the annals. Basing on historical, literary and ethnopsychological artifacts,
the author demonstrates the multifaceted personality of Boyan as a poet, artist, thinker, soldier and the
citizen of Rus-Ukraine, and also substantiates the need to celebrate Boyan’s 1000 years anniversary
in 2016 on the national and international level. В статье рассматривается гипотеза Вельтмана-
Чепы о тождественности лица Бояна и летописного
Яня. На материалах исторических, литературных,
этнопсихологических артефактов автор показывает
многогранность личности Бояна - поэта, художника,
мыслителя, воина, гражданина Руси-Украины;
обосновывает необходимость празднования
на государственном и международном уровне
1000-летнего юбилея Бояна-Яня в 2016 году.